Materials for automobile bodies - Davies, Geoff (Butterworth-Heinemann, 2012)
The selection of automobile body materials is fundamental to the choice of fabrication method, and the characteristics and performance of the final vehicle or component. The factors behind these choices comprise some of the key technological and design issues facing automotive engineers today. Materials for Automobile Bodies brings together a wealth of information on automotive materials and material technologies to provide designers and vehicle body engineers with both a solid grounding and a quick reference to inform their material choices. Coverage includes materials processing, formability, welding and joining, anti-corrosion technologies, plus a comprehensive consideration of the implications of materials selection on these processes. Dealing with the whole assembly process from raw material to production, right through to recycling at the end of a vehicle's life, this book is the essential resource for practising engineers, designers, analysts and students involved in the design and specification of motor vehicle bodies and components. Up-to-date detailed information on contemporary autobody materials, incorporating the explanation often lacking in other data-focused resources Includes informative and insightful case studies on the materials and processing choices of major OEMs, including Honda, BMW and Audi Now with more on geographical supply and usage trends, environmental concerns and end of life disassembly considerations, and how these affect selection choices.
Includes index.
Keywords: Automobiles -- Bodies -- Materials.; elektronické knihy; electronic books